Ökonomische Strategien des Naturgefahrenmanagements - Konzepte, Erfahrungen und Herausforderungen - Psenner, Roland (alpine space - man and environment, 2012)
While research on cultural dangers has a traditional focus on natural sciences the social and economic aspects of natural disasters gain increasing interest to allow for sustainable development. Hazard and loss potential need to be evaluated on a social level and alternative measures and risk provision (risk prevention and diminution of risks) as well as risk follow-up actions (diversification and risk transfer) are required. This describes a change in paradigms and a change in natural hazard management by the application of integrative risk assessment and risk management. All possible provisions need to be considered.